Self-immanent pride as the underlying source of destructive managerial anger: a conceptual proposition - Bachkirov, Alexandre A. (Journal of management, spirituality & religion, 2023)
Drawing on religious thought and critically examining psychological approaches, this paper introduces and defines the concept of self-immanent pride, a phenomenon conceived as the source of destructive managerial anger. To untangle the complexity of self-immanent pride and its anger-engendering quality, this paper ascertains the prototypical forms of self-immanent pride, elaborates on its characteristics, and posits chronically inflated self-esteem as a path from self-immanent pride to destructive managerial anger.